(untitled) (Baghdad Science Journal, 2016)
This paper includes the synthesis of some new nucleoside analogues starting with 2-substituted benzimidazole derivative (7-9), that synthesized by condensation of O-phenylenediamine with p-chloro benzaldehyde and two substituted benzoic acid , which on nucleophilic substitution with propargyl bromide gave a new N-substituted compounds (10-12). D-Fructose and D-galactose were chosen as a sugar moiety which were protected, brominated and azotated to give azido sugars (5) and (6), then they were subjected to 1,3-dipolar cycloaddition reaction with N-substuted compounds afforded bloked nucleoside analoges (13-16), which after hydrolysis gave our target the free nucleoside analogues (17-20). All prepared compounds were identified by FT-IR and some of them with 1H-NMR and 13C-NMR.